Ilhom THE INTERLEVEL ANALYSIS OF VERBAL HUMOUR RESOURCES IN THE ENGLISH LANGUAGE: THE INTERLEVEL ANALYSIS OF VERBAL HUMOUR RESOURCES IN THE ENGLISH LANGUAGE - Rustamov, Ilhom (Журнал иностранных языков и лингвистики, 2022)
Language levels are subsystems of units constituting a language hierarchy. Traditionally, four levels are distinguished, namely, phonetic, morphological, lexical and syntactical levels.